2005
DOI: 10.1353/csd.2005.0067
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effects of Student-Faculty Interaction on College Outcomes for Women and Men

Abstract: This study examined whether the impact of student-faculty interaction on a range of student outcomes—including academic achievement, goals, self-confidence, well-being, and attitudes—differed for women and men. The data were drawn from a national longitudinal sample of college students (N = 17,637) who were surveyed upon entry to college in 1994 and four years later in 1998. Results indicate that although many commonalities exist in how student-faculty interaction relates to college outcomes for women and men,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
124
3
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 23 publications
10
124
3
4
Order By: Relevance
“…Simply having contact with a faculty member appears to have positive results on students' degree aspirations (Astin, 1993;Carter, 1999;Ceja & Rivas, 2010;Endo & Harpel, 1982;Gagnon & Cocolas, 1988;Hearn, 1987;Inozu, 2011;Kim & Sax, 2009;Kuh & Hu, 2001;Pascarella, 1984;Sax, 2001;Sax, Bryant, & Harper, 2005;Varhegyi & Jepsen, 2009). Faculty interactions seem to be important across groups of students.…”
Section: Outcomes Of Good Teaching Practicesmentioning
confidence: 99%
“…Simply having contact with a faculty member appears to have positive results on students' degree aspirations (Astin, 1993;Carter, 1999;Ceja & Rivas, 2010;Endo & Harpel, 1982;Gagnon & Cocolas, 1988;Hearn, 1987;Inozu, 2011;Kim & Sax, 2009;Kuh & Hu, 2001;Pascarella, 1984;Sax, 2001;Sax, Bryant, & Harper, 2005;Varhegyi & Jepsen, 2009). Faculty interactions seem to be important across groups of students.…”
Section: Outcomes Of Good Teaching Practicesmentioning
confidence: 99%
“…This measure is a three-item factor representing students' self-assessment of their current cognitive abilities in three areas: analytical and critical thinking skills, ability to be clear and effective when writing, and ability to read and comprehend academic material (Chronbach's a = .80). College impact research has continuously demonstrated that students' growth in intellectual and cognitive skills is a function of their interaction with faculty (Astin 1993;Endo and Harpel 1982;Kuh and Hu 2001;Pascarella and Terenzini 2005;Sax et al 2005;Strauss and Terenzini 2007;Terenzini and Pascarella 1980;Volkwein et al 1986). Further, using the 2006 UCUES data, Kim and Sax (2009) confirmed the positive effects of student-faculty interaction on students' gains in critical thinking and communication skills.…”
Section: Student-level Variablesmentioning
confidence: 99%
“…decade studies in higher education have begun paying attention to ''conditional'' effects of faculty contact using disaggregated student subsamples by race, gender, and other student characteristics (e.g., Colbeck et al 2001;Cole 2004;Kezar and Moriarty 2000;Kim 2006;Kim and Sax 2009;Lundberg and Schreiner 2004;Sax et al 2005). For example, Sax et al (2005) found that, compared to female students, male students experienced greater gains in political engagement, social activism, and liberalism resulting from their interactions with faculty.…”
mentioning
confidence: 99%
See 2 more Smart Citations